Mapping mangrove degradation in Pahang river estuary, Pekan Pahang by using remote sensing - Ahmad, Zuhairi; Kassim, Zaleha; Md. Rosli, Nur Suhaila; Shammodin, Muhammad Shaheed (Zibeline International Publishing Sdn. Bhd., 2019)
This study examined the mangrove degradation in Pahang River Estuary, Pekan sub-district, Pahang between 1990 and 2017 using supervised classification. Landsat 8 OLI and Landsat 5 TM images of Pahang River Estuary have been analyzed using supervised classification and field survey. Based on the accuracy assessment, the confusion matrix for supervised classifications ranged from 77% to 81%. Kappa coefficient (K) for supervised classification ranged between the value of 0.67 and 0.72. The total mangrove covers in 2017 was 1,535.40 ha, decreased by 43.7% or 670.80 ha from its total area of 2,206.20 ha in 1990. The expansion of development area was observed in the past 27 years. Several other causes of mangrove degradation were identified during field survey, including sand mining activities along riverbank, mangrove clearing for aquaculture and agriculture. The rapid development within the coastal area and estuary had suppressed the mangroves propagation over the years. Long term monitoring of mangrove distribution is crucial to ensure the sustainability of the mangrove ecosystem.